CCLitBox. A Wikidata Gadget to Classify World Literature - Bianchini, Carlo (Journal of Information and Knowledge, 2023)
The Wikidata gadget, CCLitBox, for the automated classification of literary authors and works by faceted classification and using Linked Open Data (LOD) is presented. The tool reproduces the classification algorithm of Class O Literature of the Colon Classification and uses data freely available in Wikidata to generate Colon Classification class numbers. CCLitBox is completely free and allows any user to classify literary authors and their works. It is also easily accessible to everyone. It also uses LOD (Linked Open Data) from Wikidata where available, but if data on an author and/or their works are not available in Wikidata to be used by CCLitBox, it can be freely added, even using semi-automatic tools such as OpenRefine. Finally, CCLitBox is ready for any collaborative and networked project.